Effect of cannabis use on PTSD treatment outcomes in veterans - Meagan Petersen, PharmD, BCPP; Katherine Koller, PharmD, BCPP; Craig Straley, PharmD, BCPP; Ellen Reed, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2021)
Introduction: Researchers have found anandamide (an endocannabinoid) and cannabinoid type 1 receptor activation encourages extinction of aversive memories. Some theorize cannabinoids such as those in cannabis may provide a new treatment approach for PTSD, while others suggest it may worsen symptomology. The objective of the current study was to determine if cannabis use impacts the success of evidence-based intensive outpatient PTSD treatment in a veteran population. Methods: A list of veterans enrolled in the Battle Creek Veterans' Affairs Medical Center outpatient PTSD Clinical Team Clinic between October 1st, 2008 and October 1st, 2016 was obtained, and a random sample was identified. Study participants were veterans aged 18 to 85 years, with at least 2 PTSD Checklist scores, and a diagnosis of PTSD. Data collected included mental health medications, type and number of evidence-based psychotherapy used, and presence of co-occurring behavioral health diagnoses. The cannabis use group was compared to the no-cannabis-use group, and differences in variables pertaining to the relative number of treatment successes and failures was evaluated for statistical and clinical significance. Results: The majority of patients were white (87.1%) and male (95%). The success rate was similar between the cannabis and no-cannabis-use groups (51.9% and 51.4%, respectively). Discussion: The current study did not show that a predominantly white male veteran sample diagnosed with PTSD differed in intensive PTSD treatment success or failure based on cannabis use.